Bioactive Curcuma aromatica-stabilized silver nanoparticles embedded chitosan dressing with improved antibacterial, anti-inflammatory, and wound healing properties - M.S. Tawre; A. Padhye; S. Chakraborty; N. Kulkarni; G. Bose; S. Mittal; U. Jadhav; S. Jadhav; J.M. Rajwade; K. Pardesi (Carbohydrate Polymer Technologies and Applications)
Chronic wounds, particularly those infected with multidrug-resistant (MDR) pathogens, present significant challenges for effective healing. Silver nanoparticles (CAAgNPs) were synthsized using aqueous rhizome extract of Curcuma aromatica (CA), known for its wound-healing properties. CAAgNPs were incorporated in a chitosan (CS) dressing (CAAgNPs/CS) and tested for their wound healing potential, expecting synergistic action of AgNPs and phytochemicals capped on it. The porous nature of the CAAgNPs was confirmed using Field emission scanning electron microscopy. Fourier-transform infrared spectroscopy demonstrated a shift in peak intensity from 1589.06 to 1575.54 cm-1 for CAAgNPs/CS dressing confirming crosslinking with glutaraldehyde. Antibacterial activity of the dressings was cofirmed against isolates of Pseudomonas aeruginosa and Staphylococcus aureus. Wound healing studies were carried out using Wistar rats (six groups)- wound control, CS, CAAgNPs256/CS, CAAgNPs512/CS, CAAgNPs1024/CS, and commercial dressings. Histological examination and direct red-80 staining demonstrated maximum epithelization and collagen deposition (58.02%) within CAAgNPs1024/CS groups on day 10. Increased hydroxyproline levels (76.51 µg/mL) on day 7 for CAAgNPs1024/CS indicated maximum collagen formation. Reduced levels of inflammatory cytokines IL-6 (17.38 pg/mL) and TNF-α (80.38 pg/mL) on day 10 indicated quick wound healing without scar formation and damaging effects. The present study highlights the antibacterial and anti-inflammatory properties of CAAgNPs1024/CS dressings with a potential for wound healing applications.